Pseudo-halo nevus. - Milano, A.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
The sun is one of the exogenous stimuli able to induce nevus formation. However, nevi are not a disease, since they are present in all people. Melanoma can derive from whatever melanocyte, present in the nevi, normal skin or other extracutaneous structures. There is no reason for treating the skin covering the nevus in a different way from the rest of the skin surface (1, 2, 3, 4). Sunscreens should be applied according to the phototype and the conditions of exposure (5), irrespective of the presence of nevi and their quantity should not be greater on the nevi. A different behavior is not rational. When the sunscreen are regularly applied, they can prevent the skin from tanning naturally and adequately preparing to the impact with the sun radiations. When sunscreens for different reasons are not regularly applied, even only once, that time the skin can be found unprepared in preventing the mutagenic effect of the sun radiations and thus it can more easily suffer the negative effects of thymine and cyclopyrimidine dimers.